ANALISIS STRUKTUR NANO DARI LAPISAN TIPIS COBALT FERRITE YANG DIPREPARASI DENGAN METODE SPUTTERING - Ramli Ramli; Riri Jonuarti; Ambran Hartono (Faculty of Mathematics and Natural Sciences (FMIPA), Universitas Negeri Padang, Indonesia, 2017)
In this paper we report the results of studies relating to the synthesis of Cobalt Ferrite (CoFe2O4) thin films by a sputtering method. The CoFe2O4 thin film has been prepared onto silicon substrate from the sputtering targets, CoFe. Structural propertiesofthinfilms were characterized byx-ray diffraction and the morphology was characterized by scanning electron microscopy. The growth parameter are: base pressure 2,8 x 10-2 Torr, ratio of Argon:Oxygen flow rate are 100:50 sccm, deposition pressure 5.4 x10-1 Torr, growth temperature 100oC.Nanostructures of the thin film that have been analyzed are crystallite size and micro strain.We obtained the crystallite size of CoFe2O4 thin films for layer thickness of 40 and 48 nm, respectively are: 32 nm and 66 nm, while the micro strain is 8.0 x 10-4 and 10.2 x 10-4.